Fire Symbolism and its indications in Mahyar of Damascus’s Songs by Adunis - Ali Khezri; Rasul Balaavi; Haajar zamaani (دراسات فی اللغه العربیه و آدابها)
Ali Ahmad Said known by the pen name Adonis or Adunis is among poets who extensively use symbolism to express their ideas and thoughts.  He uses this style to express ideas and statements not directly articulated due to certain political and social restrictions.  In his symbolism, he relies on several natural elements including the sun, the sea, rainfall, the moon, stones, the sky, the wind, and fire. In this study we try to discuss and investigate the symbolism of the term “fire” and its implications in “Mahyar of Damascus’s Songs”.  The application of symbols and the use of abandoned and obsolete words and situational implications in contemporary literary texts is a more or less common trend among the poets. The main goal of the current study is to investigate the symbols and implications of the term “fire” used by Adunis and to show whether he has accepted or evaded the norms. Moreover, we try to identify positive and negative views of the poet while using this term. Accordingly, this study uses a descriptive-analytical approach. The results of the study show that, according to Aduunis, the implications of fire are divided into two main types. The first one is affirmative and positive implications which involve implications of fertility, birth, and rebirth since fire is used as a symbol of purity and cleanliness, light, transcendentalism and progress in many religions and cultures. The second category involves negative implications including destruction, devastation, and demise. These negative implications are rooted in different factors and reasons including deteriorating political conditions, war, displacement, exile, and the fact that the poet’s father died in a fire.